Effectiveness of interventions for optimising adherence to treatments for the prevention and management of scars: protocol for a systematic review and meta-analysis. Issue 3 (30th March 2019) - Killey, Jessica; Simons, Megan; Kimble, Roy M; Tyack, Zephanie
Abstract : Introduction: Treatments used in the management of scarring following wounds of the skin can be complex and time consuming, and patients may experience difficulties adhering to these treatments. Therefore, the aim of this systematic review is to identify the types of interventions that have been used to optimise adherence to treatment for preventing or reducing skin scars in adults and children and to determine the effectiveness of these interventions. Methods and analysis: Databases (PubMed, Embase, the Cumulative Index to Nursing and Allied Health Literature, PsycINFO, Web of Science and OTSeeker) will be searched using the developed search strategy to identify eligible randomised trials. Adults and children using scar treatments to prevent or manage scarring as a result of a dermal wound (which may occur following burn injury, surgery, lacerations, piercings, vaccinations, acne and other conditions affecting the skin) will be included. Any intervention with the potential to effect adherence will be included. Titles and abstracts located through searching will be screened by two independent reviewers. Full text of studies will also be screened to determine eligibility for final inclusion. Two reviewers will assess the quality of included studies using the Cochrane 'risk of bias' tool. Data extraction forms will be developed and two reviewers will extract the data. A third reviewer will be used at each stage to ensure consensus is achieved. Meta-analysis and meta-regression will be completed if appropriate, otherwise a narrative synthesis of results will be undertaken. Ethics and dissemination: No ethical approval is necessary for this systematic review as no patients will be directly involved. Results of this systematic review will be disseminated through journal publications and relevant conference presentations. PROSPERO registration number: CRD42018095082.